2006
DOI: 10.1029/2006ja011972
|View full text |Cite
|
Sign up to set email alerts
|

O(1S → 1D,3P) branching ratio as measured in the terrestrial nightglow

Abstract: [1] The branching ratio of the two optically forbidden atmospheric emission lines, O( 1 S À 1 D) at 557.7 nm and O( 1 S À 3 P) at 297.2 nm, is a fixed number in the upper atmosphere because the O( 1 S) level is common to both lines. The value for the ratio A(557.7)/A(297.2) currently recommended by NIST is 16.7, and the ratio found in the laboratory is somewhat larger. Field observations require space-based instruments, in which case calibration between the two wavelength regions is the critical issue. We circ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(25 citation statements)
references
References 61 publications
(119 reference statements)
2
23
0
Order By: Relevance
“…The transition from the first excited state of the singlet branch, 1 D, to the ground state, 3 P, produces a doublet in the red at 6300.304Å and 6363.776Å. The second excited singlet state, 1 S, decays to the 1 D state 90-95% of the time with a transition at 5577.339Å; the remaining 5-10% of the time, the 1 S state decays directly to the ground state ( 1 S -3 P) through two UV lines at 2958.365 and 2972.288Å (Slanger et al 2006a). These are all forbidden lines.…”
Section: Introductionmentioning
confidence: 99%
“…The transition from the first excited state of the singlet branch, 1 D, to the ground state, 3 P, produces a doublet in the red at 6300.304Å and 6363.776Å. The second excited singlet state, 1 S, decays to the 1 D state 90-95% of the time with a transition at 5577.339Å; the remaining 5-10% of the time, the 1 S state decays directly to the ground state ( 1 S -3 P) through two UV lines at 2958.365 and 2972.288Å (Slanger et al 2006a). These are all forbidden lines.…”
Section: Introductionmentioning
confidence: 99%
“…The green line emission allows the deduction of the atomic oxygen densities near 100 km, as shown for example by Lednyts'kyy et al (2015). The oxygen 297.2 nm line is one of the prominent components of the ultraviolet nightglow (Slanger et al, 2006), and it is produced by O( 1 S) via Reaction (R12) (Khomich et al, 2008):…”
Section: Introductionmentioning
confidence: 99%
“…However, the first Venus measurements made from a planetary orbiter (Krasnopolsky et al 1976) showed no evidence for the green line, and thus (Eastes et al 1992) compared to the Mars nightglow (lower) (Bertaux et al 2005a). The 180-260 nm NO features are identical in appearance, but the O 2 Herzberg band terrestrial features at λ > 250 nm are not reproduced at Mars it became accepted that in some manner collisions with CO 2 impede O( 1 S) observation, although it was well-known from Mariner dayglow observations that O( 1 S) is a strong feature in the UV (Barth et al 1971), and we know that the green line emission is ten times more intense (Slanger et al 2006a). However, in 1999, a ground-based Venus nightglow study demonstrated that the green line can be as intense as it is in the terrestrial atmosphere (Crisp 2001;Slanger et al 2001), although at times (as in the Venera study) it is indiscernible (Slanger et al 2006b).…”
Section: Comparative Aeronomy Of Earth/venus/marsmentioning
confidence: 94%
“…Figure 9 shows the appearance of the 180-300 nm region in the dayglow (Leblanc et al 2006a), and in addition to these two features, one sees the trans-auroral line of OI at 297.2 nm. Recent work has established that the oxygen green line at 557.7 nm, arising from the same O( 1 S) upper level, has ten times the intensity of the trans-auroral line (Slanger et al 2006a), so measurements of the latter provide estimates for the former, which in turn can be seen from terrestrial ground-based measurements, at least in the nightglow (Slanger et al 2006b). …”
Section: Mars/venus Express Studiesmentioning
confidence: 97%